Adaptation of ghrelin and the GH/IGF axis to high altitude - Riedl, Stefan; Kluge, Michael; Schweitzer, Katharina; Waldhör, Thomas; Frisch, Herwig (European journal of endocrinology, 2012)
ObjectiveHigh altitude (HA) provokes a variety of endocrine adaptive processes. We investigated the impact of HA on ghrelin levels and the GH/IGF axis.DesignObservational study as part of a medical multidisciplinary project in a mountainous environment.MethodsThirty-three probands (12 females) were investigated at three timepoints during ascent to HA (A: d −42, 120 m; B: d +4, 3440 m; C: d +14, 5050 m). The following parameters were obtained: ghrelin; GH; GH-binding protein (GHBP); IGF1; IGF2; IGF-binding proteins (IGFBPs) -1, -2, and -3; acid-labile subunit (ALS); and insulin. Weight was monitored and general well being assessed using the Lake Louise acute mountain sickness (AMS) score.ResultsGhrelin (150 vs 111 pg/ml; P<0.01) and GH (3.4 vs 1.7 μg/l; P<0.01) were significantly higher at timepoint C compared with A whereas GHBP, IGF1, IGF2, IGFBP3, ALS, and insulin levels did not change. IGFBP1 (58 vs 47 μg/l; P<0.05) and, even more pronounced, IGFBP2 (1141 vs 615 μg/l; P<0.001) increased significantly. No correlation, neither sex-specific nor in the total group, between individual weight loss (females: −2.1 kg; males: −5.1 kg) and rise in ghrelin was found. Five of the subjects did not reach investigation point C due to AMS.ConclusionsAfter 14 days of exposure to HA, we observed a significant ghrelin and GH increase without changes in GHBP, IGF1, IGF2, IGFBP3, ALS, and insulin. Higher GH seems to be needed for acute metabolic effects rather than IGF/IGFBP3 generation. Increased IGFBP1 and -2 may reflect effects from HA on IGF bioavailability.